Vitamin B12 and its binding proteins in hepatocellular carcinoma and chronic liver diseases. (September 2014) - Simonsen, Kira; Rode, Anthony; Nicoll, Amanda; Villadsen, Gerda; Espelund, Ulrick; Lim, Lucy; Angus, Peter; Arachchi, Niranjan; Vilstrup, Hendrik; Nexo, Ebba; Grønbæk, Henning
Abstract Background. The vitamin B12 (B12)-binding protein haptocorrin (HC) has proven to be a potentially useful biomarker in patients with fibrolamellar hepatocellular carcinoma (HCC). Little is known concerning the level of HC and other B12-related proteins in patients with HCC as compared to patients with other chronic liver diseases (CLDs) and healthy controls. We hypothesized that HC could be a biomarker of HCC. Aims. To investigate levels of HC and B12-related proteins in HCC compared to CLDs and healthy controls. Methods. We investigated two patient populations: A cross-sectional cohort of HCC patients (n = 130), CLD patients (n = 102) and healthy controls (n = 46) and a cohort of 38 HCC patients studied at baseline and 1, 4, and 12 weeks following ablative treatment. Patients were evaluated by standard biochemistry, Child–Pugh-score and Barcelona Clinic Liver Cancer (BCLC) classification. We analyzed total B12 by routine methods and HC, transcobalamin (TC), B12 saturated TC (holoTC), and the soluble cell surface receptor for holoTC (sCD320) by in-house enzyme-linked immunosorbent assay. Results. HC showed higher median (range) levels for both HCC (590 [290–5860]) and CLD patients (620 [310–4010]) compared to controls (460 [250–2020]) (p < 0.01). Total B12, TC, holoTC, and sCD320 showed elevated levels in both HCC and CLD compared to controls. Only holoTC changed following treatment, without a concurrent change in TC. Conclusion. B12 and B12-related proteins (total B12, HC, TC, holoTC, and sCD320) show elevations in both HCC and CLD patients compared to controls, suggesting a relation to CLD in general rather than to primary liver cancer. Thus, HC is not useful as a biomarker for HCC.